Minds, Hearts, and Bodies, Not Data Points: A Response to Harris, McDonald, and Sparks's "Sexual Harassment in the Military: Individual Experiences, Demographics, and Organizational Contexts". Issue 3 (July 2019) - Buscha, Connie A.
Harris, McDonald, and Sparks's recent quantitative research article, Sexual Harassment in the Military: Individual Experiences, Demographics, and Organizational Contexts, does not deliver its title's promises. In 2018, social science research investigating, describing, and, ultimately, impacting human lives has advanced beyond overly simplistic figures of data points on x - and y -axes and rhetorical findings. Therefore, this response challenges numerous aspects of Harris, McDonald, and Sparks's article. It identifies pragmatism as a valuable theoretical perspective from which to investigate the phenomenon of sexual harassment in the military. It further asserts that a qualitative methodology best provides rich, nuanced, and descriptive data from which researchers and scholars can identify measures to mitigate negative experiences for all service members regardless of gender.